2001
DOI: 10.1037/1040-3590.13.4.531
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and ethnicity: Structural, item, and test generalizability of the Psychopathy Checklist—Revised (PCL-R) in Caucasian and African American participants.

Abstract: The Psychopathy Checklist-Revised (PCL-R) is an important measure in both applied and research settings. Evidence for its validity is mostly derived from male Caucasian participants. PCL-R ratings of 359 Caucasian and 356 African American participants were compared using confirmatory factor analysis (CFA) and item response theory (lRn analyses. Previous research has indicated that 13 items of the PCL-R can be described by a 3-factor hierarchical modeL This model was replicated in this sample. No cross-group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
182
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(196 citation statements)
references
References 49 publications
11
182
0
3
Order By: Relevance
“…As noted previously, there have been some differences noted in the overall rate of CU traits (Skeem et al 2004) and in the relation between certain items and the overall construct (Cooke et al 2001) between Caucasian and African-American samples. These findings have led some researchers to suggest that the meaning of the items on CU scales may be different for some African-American and Caucasian individuals (Sullivan and Kosson 2006).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…As noted previously, there have been some differences noted in the overall rate of CU traits (Skeem et al 2004) and in the relation between certain items and the overall construct (Cooke et al 2001) between Caucasian and African-American samples. These findings have led some researchers to suggest that the meaning of the items on CU scales may be different for some African-American and Caucasian individuals (Sullivan and Kosson 2006).…”
mentioning
confidence: 68%
“…The few studies that have utilized samples with significant minority representation in both adult (Richards et al 2003) and adolescent (Hicks et al 2000;Kruh et al 2005) offending samples have shown comparable associations between CU traits and severity of offending. However, there is also evidence that measures of these traits may show differences at both item and scale level across ethnic groups (Cooke et al 2001;Skeem et al 2004). Also, some of the correlates to CU traits have not generalized across ethnic groups (Kimonis et al 2006;Lorenz and Newman 2002).…”
mentioning
confidence: 99%
“…Another limitation is the distribution of the full scale intelligence scores, which is representative for UK prison populations (Copestake et al, 2013), but might not necessarily hold for Northern American prison populations, which have been found to be comparably lower (Cooke et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Criteria that demonstrate DCF need not reflect bias or variance across subgroups if the DCF occurs in opposing directions (e.g., some criteria result in greater discrimination or severity among men while others demonstrate the opposite effect) (Cooke et al 2001;Bolt et al 2004). Whether DCF actually reflects invariance across subgroups can be determined if the observed criterion-level DCFs cancel out at the total test (scale) score level.…”
Section: Discussionmentioning
confidence: 99%